Pengaruh Persepsi Keadilan Terhadap Kepuasan Pasca Pemulihan Kegagalan Pada Restoran PIZZA HUT - Pratiwi, Rai Gita; mandala, kastawan (E-Jurnal Manajemen; Vol 3 No 8 (2014), 2014)
Service recovery is a key to change an unsatisfied customer become a satisfied customer who satisfied with the company services. Satisfaction after recovery be able judge from three dimensions of percieved justice which distributive justice, procedural justice and interactional justice. The purpose of this study is to investigate the effects of distributive justice, procedural justice, and interactional justice on customer satisfaction after recovery. Regression test was used to test the hypotheses with data from 104 unsatisfied customer. The findings showed that customer satisfaction after recovery was positive and significantly affected by perceived justice (distributive justice, procedural justice and interactional justice). Based on that results, Pizza Hut need to optimaze distributive justice with giving compensation more variably, procedural justice with giving recovery more flexsibly, and interactional justice with giving customer more reasonable information for service failures.
Keywords: satisfaction after recovery, service failures, service recovery, distributive justice, procedural justice, interactional justice